Desain Implementasi Aplikasi Wisata Kuliner Halal Berbasis Android Pada Kota Batam - Andi Supriadi Chan; Yera Wahda Wahdi (LPPM Universitas Putera Batam, 2018)
Batam city is one of the islands which often passed by Indonesian society, especially transit want to go to Singapore and Malaysia.hal state is caused by island of batam directly adjacent to country of singapore and malaysia ,. This causes a lot of cultural mixing and tastes of people in the city batam. Culinary that has halal certification began to become a trend that began to be searched at this time, growth for the market of halal products in 2012 in Asia reached USD 418.1 billion, In the city of Batam. People who live in this city are Heterogeneous inhabited by various tribes, religions, races and groups, it is a bit difficult for people who are Islamic in searching for food labeled kosher. So it can be solved by making a culinary application based on android.Aplikasi this will guide from the location or position where they are to the destination to be visited. This application can also provide information related to halal culinary, so that users can choose culinary which is desirable and in accordance with the tastes so that this app is expected to be able to help people in finding food that is labeled kosher in batam city so that no difficulty in visiting batam city whenever and wherever they are. so the first new tourist kalipun visit to batam can easily looking for halal culinary with their android smartphone by using halal culinary app available at playstore.